Isolation Of ß-Lactoglobulin and a-Lactalbumin from whey - Mohd Mazlan, Mohamed (2010)
Whey is a byproduct in cheese production.Whey solution is rich with proteins;the main proteins in whey are β-Lactoglobulin(β-Lg)(50%),α-Lactalbumin(α-La)(20%),bovine serum albumin(BSA)(10%) and immunoglobulin’s(Igs)(10%). Single protein has higher value then whey solution and has specific application.Hence this paper aims to isolate two of main whey proteins that are β-Lg and α-La due to their functions and higher value of pure protein.In this work, whey was prepared during casein coagulation from skim milk by acidic precipitation at pH below than 5 with 0.5 M hydrochloric acid.The experiments were conducted by AKTA Fast Protein Liquid Chromatography(FPLC),using size exclusion(packed by superdex TM 75 gel filtration media in an empty size exclusion XK column (60 ml))and cation exchange column(HiTrap SP HP,1ml column)in order to isolate both proteins from whey and 10% separating gel of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDSPAGE) was used to identify each protein form isolation steps and to determine the degree of purity of β-Lg and α-La.Silver staining was used in developing protein band on SDS gel.The experimental results concluded that both β-Lg and α-La can be isolated from other proteins in whey by using size exclusion and cation exchange fast protein liquid chromatography.Both β-Lg and α-La were visualized at 18 kDa and 14 kDa respectively, in SDS-PAGE.